ABANDONED FISHING GEARS IMPACT ON CORALLIGENOUS REEFS OF CAPO CARBONARA MARINE PROTECTED AREA - Azzola, Annalisa; Atzori, Fabrizio; Cadoni, Nicoletta; Carosso, Lara; Garcia Gutiérrez, Maria Leonor; Mancini, Ilaria; Atzeni, Viola; Oprandi, Alice; Paoli, Chiara; Povero, Paolo; et al. (Biologia Marina Mediterranea, 2024)
Fishing gears can cause several damages on coralligenous reefs not only during fishing activities, but also when they are lost on the seafloor. The removal of abandoned fishing gears (AFG) is debated: this may cause further damage on marine habitats. With the aim of assessing the impact of AFG removal on coralligenous in the Capo Carbonara Marine Protected Area (MPA), five sites were monitored considering impact stations and control stations. The BACI (Before-After/Control-Impact) sampling design was used to compare the ecological status of coralligenous before and after the AFG removal by applying the COARSE index (Coralligenous Assessment by Reef Scape Estimate). A reduction of ecological status was observed only in the impact stations of two sites. Gorgonians, bryozoans and erect algae were the most affected species by the action of AFG, the removal of which is recommended when it is done in a way that does not create further damages.